Warehouse Re-Layout for a Third-Party Logistics Provider Based on Shipping Patterns Using the Apriori Algorithm - Hidayatuloh, Syarif; Br Tarigan, Jenni; Noor Qisthani, Nabila (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
Warehouse operations face challenges that affect efficiency. PT ABC, a third-party logistics provider, has been experiencing these issues due to an unstructured warehouse layout. It leads to inefficient movement and delayed deliveries. This study aims to re-design the warehouse layout of PT ABC based on shipping patterns using the apriori algorithm. Shipment data from January to June 2024 was analyzed using the apriori algorithm with a minimum support of 30% and a confidence level of 50% to find frequently shipped item combinations. One of the strong associations found was between "Mechanical Components" and "Spare Parts," with a lift value of 1.68. Based on the results, a proposed layout was developed by considering both the FSN (Fast, Slow, Non-moving) classification and apriori findings. The effectiveness of the new layout was evaluated using rectilinear distance calculations, which showed a reduction in total item movement distance from 45,952 meters to 44,343 meters.